Strengthening the non-pre-irradiated near-infrared mechanoluminescence of CaZnOS:Nd3+ by Mn2+ coactivation for biomechanical imaging. Issue 10 (27th February 2023) - Lei, Jianxiong; Li, Wei; Tang, Yiqian; Cai, Yiyu; Wang, Shanshan; Dou, Kunpeng; Zhang, Jun-Cheng
Abstract : Doping of Mn 2+ greatly enhances the non-pre-irradiated near-infrared mechanoluminescence (NIR ML) of CaZnOS:Nd 3+ by energy transfer from the host to Mn 2+ to Nd 3+ . This effect allows the acquisition of NIR ML images with high signal-to-background ratios in biomechanical imaging. Abstract : The development of lanthanide-activated CaZnOS mechanoluminescent (ML) phosphors that can produce non-pre-irradiated mechanoluminescence (ML) in the near-infrared (NIR) region opens a new avenue for in vivo and in situ biomechanical imaging. However, the progress in obtaining NIR ML images with a high signal-to-background ratio (SBR) has been constrained by the difficulties in achieving intense NIR ML. In this paper, we report a Mn 2+ -coactivation induced dual sensitization strategy that combines host sensitization with dopant sensitization to enhance the NIR ML of CaZnOS:Nd 3+ . Systematic characterization of the CaZnOS:Nd 3+, Mn 2+ series reveals that the enhanced NIR ML arises from the energy transfer from the host to Mn 2+ to Nd 3+, which involves the Mn 2+ -doping strengthened host excitation and the resonant energy transfer from Mn 2+ to Nd 3+ . We demonstrate that the developed CaZnOS:Nd 3+, Mn 2+ phosphor greatly enhances the transient intensity of the NIR ML response and the SBR value of NIR ML images through a series of NIR ML penetration experiments on chicken breast and human cheek. In particular, the transient NIR ML response to dental occlusion is improved by 368%, while the SBR value of NIR ML penetrating the human cheek is improved from 1.25 to 2.1. Our results are expected to provide new insights into the development and optimization of non-pre-irradiated NIR ML phosphors, and further to advance the applications of NIR ML phosphors with an intense emission for high SBR biomechanical imaging.